2021
DOI: 10.31234/osf.io/39rbs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple timescales of temporal context in risky choice: Behavioral identification and relationships to physiological arousal

Abstract: Context-dependence is fundamental to risky monetary decision-making. A growing body of evidence suggests that temporal context, or recent events, alters risk-taking at a minimum of three timescales: immediate (e.g. trial-by-trial), neighborhood (e.g. a group of consecutive trials), and global (e.g. task-level). To examine context effects, we created a novel monetary choice set with intentional temporal structure in which option values shifted between multiple levels of value magnitude (“contexts”) several time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 67 publications
5
14
0
Order By: Relevance
“…This research indicates that the current option values and probabilities as well as previous outcomes are important to risky choice behavior. In a recent set of studies, we found that risk-taking decreased following large positive previous outcomes 6 and replicated this effect in a subsequent novel dataset 21 .That risk-taking decreased following large previous outcomes is consistent with some previous studies 5,11 but at odds with others showing increased risk-taking 9,14,16,17 following large gains. Such inconsistencies in the literature may be the result of differences in how outcomes are realized across tasks 10 and integrated with potential future outcomes 17 .…”
Section: Multiple Timescales Of Temporal Context Effects In Risky Dec...supporting
confidence: 89%
“…This research indicates that the current option values and probabilities as well as previous outcomes are important to risky choice behavior. In a recent set of studies, we found that risk-taking decreased following large positive previous outcomes 6 and replicated this effect in a subsequent novel dataset 21 .That risk-taking decreased following large previous outcomes is consistent with some previous studies 5,11 but at odds with others showing increased risk-taking 9,14,16,17 following large gains. Such inconsistencies in the literature may be the result of differences in how outcomes are realized across tasks 10 and integrated with potential future outcomes 17 .…”
Section: Multiple Timescales Of Temporal Context Effects In Risky Dec...supporting
confidence: 89%
“…Below, we report how we determined the sample size, and all data exclusions, manipulations, and study measures. Data from this paper can be accessed at: https://osf.io/a7nvx/ [48]. For all data cleaning and analysis scripts: https://github.com/sokolhessnerlab/vic [49].…”
Section: Methodsmentioning
confidence: 99%
“…Data from this paper can be accessed at: https://osf.io/a7nvx/ [48]. For all data cleaning and analysis scripts: https://github.com/sokolhessnerlab/vic [49]. Data were analyzed using the package "lme4" [50] in R, version 4.0.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from this paper can be accessed at: https://osf.io/a7nvx/ (Brooks & Sokol-Hessner, 2021a). For all data cleaning and analysis scripts: https://github.com/sokolhessnerlab/vic (Brooks & Sokol-Hessner, 2021b). Data were analyzed using the package "lme4" (Bates, Maechler, Bolker, & Walker, 2015) in R, version 4.0.0.…”
Section: Methodsmentioning
confidence: 99%